Tracing Back the Weather Origins of Human Welfare : Evidence from Mozambique - Baez, Javier E.; Caruso, German; Niu, Chiyu (World Bank, Washington, DC, 2017)
Mozambique is among the African countries most exposed to weather-related hazards. Using detailed gridded precipitation data for individuals' birth-year and birth-district, this study investigates the effects of extreme rainfall anomalies around the time of birth on long-run well-being. The results show that the socioeconomic outcomes of adults are influenced by weather shocks that occur early in life. Individuals exposed to floods while in utero or during the first year of life are less likely to participate in the labor market. Consequently, the households that they are heading exhibit lower consumption and are more prone to be poor. In disentangling the mechanisms at play, this paper presents suggestive evidence of variation in agricultural output, food security, and subsequent detrimental effects on human capital accumulation as important drivers behind the impacts. The study concludes that policy efforts aimed at accelerating poverty reduction in Mozambique will have to consider the inability of rural households to shield the well-being of children from the consequences of extreme weather shocks.